RESVERATROL DIMERS FROM STEM BARK OF Hopea gregaria AND THEIR CYTOTOXIC PROPERTIES - Sahidin Sahidin; Euis Holisotan Hakim; Yana Maolana Syah; Lia Dewi Juliawaty; Sjamsul Arifin Achmad; Laily Bin Din; Jalifah Latip (Indonesian Journal of Chemistry, 2008)
Six resveratrol dimers have been isolated from the stem bark of H. gregaria, ampelopsin A (1), balanocarpol (2), ε-viniferin (3), hopeafuran (4), heimiol A (5), and parviflorol (6). The structures of these compounds were determined based on spectroscopic evidence such as UV, IR, 1-D, 2-D NMR and comparison with the reported data. These compound inventions are strengthen conclusion that Hopea tends to produce resveratrol dimers. Biological activity of those compounds against murine leukemia P-388 cells showed that ε-viniferin (3) is the most active compound with IC50 value 5.1 ± 0.3 μg/mL.